2010
DOI: 10.1590/s1806-83242010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone area and bone healing in spontaneously hypertensive rats: a histometric study

Abstract: Abstract:Clinical and experimental studies have demonstrated some negative effect of hypertension on bone mineral density. The aim of this study was to evaluate bone healing and trabecular bone area (TBA) in spontaneously hypertensive rats (SHR), a well-established model of essential hypertension, when compared to normotensive rats (NTR). A critical-size defect was surgically created in the right tibia of SHR (n = 12) and normotensive rats (NTR; n = 12), while the contralateral tibia was left intact. Eight day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
0
19
1
1
Order By: Relevance
“…[3][4][5] Our results are not in accordance with those of Antolic et al, 15 who have reported benefi cial effects of Cr supplementation on the bone mass of Sprague Dawley rats. Some methodological differences can explain the contradictory results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Our results are not in accordance with those of Antolic et al, 15 who have reported benefi cial effects of Cr supplementation on the bone mass of Sprague Dawley rats. Some methodological differences can explain the contradictory results.…”
Section: Discussioncontrasting
confidence: 99%
“…1,2 There is evidence of a reduction in bone mineral density (BMD) in that model, resulting from changes in calcium metabolism, which cause an increase in bone resorption. [3][4][5] While the bone mass of healthy Sprague Dawley rats peaks around the age of 30-36 weeks, SHRs stabilize their bone growth at the age of only 18 weeks. In addition, the peak bone mass in SHRs is approximately 40 mg/cm 2 lower than that in healthy rats.…”
Section: Introductionmentioning
confidence: 99%
“…In a ligature-induced periodontitis model and increased RANKL/OPG ratio toward a more osteoclastic condition was observed in the SHR rats versus normotensive controls. 20,21 Hypertension may also negatively affect bone mineral density due to abnormal metabolism of 1,25-dihydroxyvitamin D, a key regulator of calcium homeostasis and bone metabolism, intestinal calcium transport, and angiotensin II-mediated osteoclast activation.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,20,21,22 Few studies can be found correlating endodontic disease and hypertension. Allareddy et al, 23 conducted a retrospective study where they found that 24.6% of patients hospitalized for periapical abscesses were hypertensive.…”
mentioning
confidence: 99%
“…Moreover, evidence suggests that the WKY strain is not the most suitable for backcross studies due to incidence of spontaneous hypertension and somewhat higher levels of blood pressure in these rats 1,2,19,24 . According to several studies 3,11,15,17 , SHRs were compared to Wistar rats, which are safely normotensive and have no genetic alteration that could modulate arterial pressure.…”
Section: Discussionmentioning
confidence: 99%